Faktor-Faktor yang Memengaruhi Tekanan Darah pada Remaja Sekolah Menengah Pertama di Jakarta Tahun 2025: Blood Pressure and Its Associated Factors Among Junior High School Students in Jakarta, 2025 - Cumayo Putri Riode; Iin Fatmawati; Sintha Fransiske Simanungkalit (Universitas Airlangga, 2025)
Background: Hypertension is a condition characterized by persistently elevated arterial blood pressure and is associated with an increased risk of future cardiovascular disease. This condition is no longer confined to adult populations but has increasingly been identified among adolescents. Key determinants contributing to the development of adolescent hypertension include unbalanced dietary patterns and unhealthy lifestyle behaviors. Objectives: To analyze the factors associated with blood pressure levels among adolescents attending SMP Negeri 182 Jakarta in 2025. Methods: An observational study with a cross-sectional design was conducted using stratified random sampling. The study involved 217 students enrolled at SMP Negeri 182 Jakarta. The main variables assessed included the frequency of Ultra-Processed Foods (UPF) consumption, Body Mass Index-for-age (BMI-for-age), and Mid-Upper Arm Circumference (MUAC). Data were collected through face-to-face interviews using structured questionnaires and anthropometric measurements. Statistical analyses comprised univariate analysis, bivariate analysis using Spearman’s correlation test, and multivariate analysis using logistic regression. Results: Bivariate analysis demonstrated significant correlations between BMI-for-age (p-value=0.000) and MUAC (p-value=0.000) with systolic blood pressure, as well as with diastolic blood pressure. Furthermore, multivariate analysis confirmed that BMI-for-age was the primary factor associated with both systolic (p-value=0.000; OR=2.201; 95% CI=1.670–2.899) and diastolic blood pressure (p-value=0.000; OR=3.373; 95% CI=1.761–6.461). Conclusions: BMI-for-age was identified as the main factor associated with increased blood pressure levels among adolescents at SMP Negeri 182 Jakarta in 2025. Therefore, early monitoring of nutritional status is crucial to prevent the future risk of hypertension.